Review Article: Aktivitas Farmakologi Senyawa Karbohidrat bagi Kesehatan - Pingky Valentina; Bertha Rusdi; Farendina Suarantika (Bandung Conference Series: Pharmacy, 2024)
Abstract. Carbohydrates are one of the essential macronutrients that play a crucial role in the human body. They not only provide the main source of energy but also support various biological functions. This study aims to examine the activity of carbohydrate compounds and their health benefits through a systematic literature review (SLR) method. The articles reviewed were limited to publications from 2015 onwards and accessed through Google Scholar. The results showed that carbohydrate compounds, such as beta-glucan from black yeast, have important biological activities such as blood glucose regulation and the enhancement of PI3K and IRS expression. Additionally, carbohydrate compounds from the sea, such as laminarin, chitosan, and fucoidan, exhibit antioxidant, anti-inflammatory, anticoagulant, antitumor, and antimicrobial activities. The research also highlights the importance of glucose as the primary energy source for the human brain and the potential of ribose derivative compounds as significant antitumor agents. Overall, this study confirms the importance of consuming carbohydrates from healthy sources in supporting heart health, controlling body weight, and maintaining energy balance and a healthy gut microbiota. These findings can serve as a scientific basis for more detailed and personalized dietary recommendations in efforts to maintain health and prevent disease. Abstrak. Karbohidrat adalah salah satu makronutrien esensial yang memiliki peran penting dalam tubuh manusia. Mereka tidak hanya menyediakan energi utama, tetapi juga mendukung berbagai fungsi biologis. Penelitian ini bertujuan untuk mengkaji aktivitas senyawa karbohidrat dan manfaat kesehatannya melalui metode tinjauan literatur sistematis (SLR). Artikel yang ditinjau dibatasi pada publikasi dari tahun 2015 ke atas dan diakses melalui Google Scholar. Hasil penelitian menunjukkan bahwa senyawa karbohidrat, seperti beta-glukan dari black yeast, memiliki aktivitas biologis penting seperti regulasi glukosa darah dan peningkatan ekspresi PI3K dan IRS. Selain itu, senyawa karbohidrat dari laut, seperti laminaran, kitosan, dan fukoidan, menunjukkan aktivitas antioksidan, antiinflamasi, antikoagulan, antitumor, dan antimikroba. Penelitian juga mengungkapkan pentingnya glukosa sebagai sumber energi utama bagi otak manusia, serta potensi senyawa ribosa derivatif sebagai agen antitumor yang signifikan. Secara keseluruhan, penelitian ini menegaskan pentingnya konsumsi karbohidrat dari sumber sehat dalam mendukung kesehatan jantung, mengontrol berat badan, dan menjaga keseimbangan energi serta mikrobiota usus yang sehat. Temuan ini dapat menjadi dasar ilmiah untuk rekomendasi diet karbohidrat yang lebih detail dan personal dalam upaya menjaga kesehatan dan mencegah penyakit.